Pengembangan Teknologi Proses Produksi Bionanokomposit Filler Biomassa Rotan - Siti Nikmatin; Lisdar Idwan Sudirman; Mersi Kurniati (Institut Pertanian Bogor, 2014)
Rattan biomass is a fiber waste from processing industry of rattan. Its abundant availability, as well as does not threaten the balance of food and feed, make it a potential source as raw material for composite filler of cellulose nanoparticles. To obtain a high cellulose content, it was inoculated with White rote fungi and Aspergillus niger. The experiments were conducted at inoculation time of 15, 21, and 30 days. The results showed that biomass of rattan extracted with White rote fungi and Aspergillus niger reached maximum cellulose content at the inoculation time of 21 days ie 76.47% cellulose, lignin 2.39%, and 20% moisture content. Cellulose has a monoclinic crystal structure, a =7.87; b=10.31; c=10.13 α= γ = 90, β=120. Nanoparticles were produced by disk mill-hummer mill method with variation milling time of 15, 30, and 45 minutes. Collision, friction, and heat for 30 minutes of milling could produce energy that was transferred to the particles and caused cavitation which resulted particles of 16.22-51.30 nm particle size. Production of test piece and prototype of nanocomposite using TSE and injection molding produced material which has 2 phases of crystal structure, namely monoclinic, and orthorhombic phases. The mechanical properties of impact strength was 67.769 J/m and hardness of 79.97 HRR. Thermal properties and density of bionanokomposit showed comparable values with synthetic composites.